Lactosylated IR820/DOX Co-Assembled Nanodrug for Synergetic Antitumour Therapy - Jiang Y (Dove Medical Press, 2020)
Yue Jiang,1 Chunzhi Huang,1,2 Yuxia Luan1 1Department of Pharmaceutics, Key Laboratory of Chemical Biology (Ministry of Education), School of Pharmaceutical Sciences, Shandong University, Jinan, Shandong Province, People’s Republic of China; 2Department of Pharmacy, Third Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of ChinaCorrespondence: Yuxia LuanDepartment of Pharmaceutics, Key Laboratory of Chemical Biology (Ministry of Education), School of Pharmaceutical Sciences, Shandong University, 44 Wenhuaxi Road, Jinan, Shandong Province 250012, People’s Republic of ChinaTel +86 531-88382007Fax +86 531-88382548Email yuxialuan@sdu.edu.cnIntroduction: Synergistic treatment integrating photothermal therapy (PTT) and chemotherapy is a promising strategy for hepatocellular carcinoma (HCC). However, the most commonly used photothermal agent, IR820, and chemotherapeutic drug, doxorubicin hydrochloride (DOX), are both hydrophilic molecules that suffer from the drawbacks of a short circulation time, rapid elimination and off-target effects.Methods and Results: Herein, a novel nanodrug that combined HCC-targeted IR820 and DOX was developed based on excipient-free co-assembly. First, lactosylated IR820 (LA-IR820) was designed to target HCC. Then, the LA-IR820/DOX nanodrug (LA-IR820/DOX ND) was purely self-assembled without excipient assistance. The physicochemical properties and the chemo-photothermal antitumour activity of the excipient-free LA-IR820/DOX ND were evaluated. More importantly, the obtained LA-IR820/DOX ND exhibited 100% drug loading, remarkable HCC targeting and excellent antitumour efficacy.Conclusion: This excipient-free LA-IR820/DOX ND may be a promising candidate for the synchronous delivery and synergistic targeting of IR820 and DOX as a combined chemo-photothermal therapy.Keywords: excipient-free, hepatoma cell targeting, self-assembly nanodrug, photothermal therapy, chemotherapy